Selected styles in web-based educational research - Mann, Bruce Leslie 1950-.; Gale Group (Hersey, Penn. Information Science Pub., 2006)
"This book is intended for prospective web teachers and trainers interested in conducting Web-based educational research"--Provided by publisher.
Research on educational technology policy in the United States, Australia, Canada, and the European Union -- Internet technology and educational research -- Conducting case study educational research on the Web -- Conducting action research with Web tools -- Exploring the complexities in online formative evaluations -- Conducting experimental research on online teaching and learning -- Conducting qualitative educational research on the Web -- Virtual ethnography and discourse analysis -- Conducting correlational research on the Web.
Electronic reproduction.
Keywords: Education -- Research -- Methodology; Web-based instruction -- Research -- Methodology; Educational technology -- Government policy; Electronic books